The Fiqh al-Ṭawāri’ Thoughts of ‘Abd Allah Bin Bayyah on the Management of Worship during the COVID-19 Pandemic - Harun, Muhammad Safwan; Nor Mohd Zulkarnain, Saiful Islam; Ali, Abdul Karim; Zainal Abidin, Mohd Syukri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The COVID-19 pandemic that struck the world recently had left a huge impact on all sectors of life. The outbreak of the virus resulted in a no-physical contact form of human interaction as a measure of curbing its cycle of transmission. The impact was also felt in religious practice and worship due to the closure of mosques which resulted in the suspension of congregational prayers and other religious activities. This state of affairs led to discord in the religious spirit of the community since the new rulings conflicted with their religious interests. There were public disputes over the provisions of Islamic primary rulings, especially in matters of worship, albeit these were declared by the authorities such as the fatwa institution. Thus, the purpose of this study was to identify the principles of Islamic primary rulings during an epidemic using the fiqh al-ṭawāri’ discourse framework of Shaykh ‘Abd Allah bin Bayyah. Based on these principles, an assessment was conducted on the conflicting Islamic primary rulings in Malaysia during the epidemic. To achieve the objective, library data from the Fiqh al-ṭawāri’ Discourse held in 2020 was fully used. Data were analysed inductively, deductively and comparatively using the content analysis method. It was concluded that the fiqh al ṭawāri’ framework was not based on the circumstances of the epidemic, instead it was the outcome of an ijtihad which had a reliable source and methodology in Sharia.